Determinants of Trade Balance in Peru: An Empirical Analysis Using Multiple Linear Regression (Eurasian Journal of History, Geography and Economics, 2024)
This study presents a summary overview of the trade balance and its determinants in Peru. To better understand the case, previous studies, and other bibliographic sources were used. To examine the effect of the Real Effective Exchange Rate (REER), net Foreign Direct Investment (FDI), real Gross Domestic Product (GDP), domestic income, and inflation on the behavior of the trade balance of the country, the Multiple Linear Regression model (MLR) was utilized. The data was obtained from the following databases: Worldbank, and Federal Reserve Bank of St. Louis (FRED). The main conclusion is that REER, domestic income, and inflation negatively influence the trade balance. Inflation is proven to have little impact on the trade balance. The recommendations of the paper are to stabilize REER and imply export-boosting policies.